2022
DOI: 10.1111/aor.14372
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term normothermic perfusion of human livers for longer than 12 days

Abstract: In this case report, we preserved human livers for up to 13 days under normothermic conditions using a modified commercial perfusion system. Two whole livers were split into two left lateral segment grafts and two extended right grafts without interruption to blood flow and then perfused on separate machines. Not only does this provide the basis for a meaningful study of liver function in the long term, but this could also facilitate the development of a model of ex situ liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…In their novel circuit, they identified the need for strict glucose regulation, dialysis, and control of haemolysis to achieve a 7-day preservation of porcine and human livers [69]. More recently, Lau et al reported the successful ex situ normothermic preservation of a split human liver graft for 13 days [70]. A group from Sydney attributed their success to a dialysis filter for toxin removal and an air-oxygen gas blender for intensive regulation of acid-base balance [70].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their novel circuit, they identified the need for strict glucose regulation, dialysis, and control of haemolysis to achieve a 7-day preservation of porcine and human livers [69]. More recently, Lau et al reported the successful ex situ normothermic preservation of a split human liver graft for 13 days [70]. A group from Sydney attributed their success to a dialysis filter for toxin removal and an air-oxygen gas blender for intensive regulation of acid-base balance [70].…”
Section: Future Directionsmentioning
confidence: 99%
“…More recently, Lau et al reported the successful ex situ normothermic preservation of a split human liver graft for 13 days [70]. A group from Sydney attributed their success to a dialysis filter for toxin removal and an air-oxygen gas blender for intensive regulation of acid-base balance [70]. Thus, prolonged perfusion in the clinical context may soon become a reality.…”
Section: Future Directionsmentioning
confidence: 99%
“…The liver was split ex-vivo with continuous dual perfusion using the technique we have previously described. [9][10][11] In brief, the liver was divided into a left lateral segment graft (LLSG, segments 2 and 3) and an extended right graft (ERG, segments 1 and 4-8). The coeliac trunk was allocated to the LLSG, and the main portal vein was kept with the ERG.…”
Section: Perfusion Protocolmentioning
confidence: 99%
“…We modi ed a commercial liver perfusion system (Liver assist, Xvivo, Gronigen, Netherlands) as previously described using commercially-available equipment. [9][10][11] This system utilises a dual-pump con guration with an open venous reservoir and thermoregulatory unit. The modi cations are summarised in Fig.…”
Section: Modi Ed Perfusion Machinementioning
confidence: 99%
See 1 more Smart Citation